2013
DOI: 10.1093/mnras/stt2101
|View full text |Cite
|
Sign up to set email alerts
|

The variable ionized absorber in the Seyfert 2 Mrk 348

Abstract: We present the results of the analysis of the X-ray spectrum of the Seyfert 2 Mrk 348, observed by Suzaku and XMM-Newton. The overall spectrum of Mrk 348 can be described by a primary power law continuum seen through three layers of absorption, of which one is neutral and two are ionised. Comparing Suzaku (2008) and XMM-Newton (2002) observations we find variability of the X-ray spectral curvature. We suggest that the variability can be explained through the change of column density of both the neutral and one… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 75 publications
(78 reference statements)
1
7
0
Order By: Relevance
“…We recall that variations are not due to changes in the power law index, Γ, but related to its normalization. It has been shown that hard X-ray variability is usual in Seyfert 2 galaxies (e.g., Turner et al 1997;Trippe et al 2011;Marchese et al 2014). In fact, this kind of variation has already been reported in the literature for objects included in the present work from intrinsic flux variations indicating changes in the nuclear continuum (Isobe et al 2005) or because they needed to set free the normalization of the power law for a proper fit to the data (LaMassa et al 2011).…”
Section: Flux Variationssupporting
confidence: 62%
See 4 more Smart Citations
“…We recall that variations are not due to changes in the power law index, Γ, but related to its normalization. It has been shown that hard X-ray variability is usual in Seyfert 2 galaxies (e.g., Turner et al 1997;Trippe et al 2011;Marchese et al 2014). In fact, this kind of variation has already been reported in the literature for objects included in the present work from intrinsic flux variations indicating changes in the nuclear continuum (Isobe et al 2005) or because they needed to set free the normalization of the power law for a proper fit to the data (LaMassa et al 2011).…”
Section: Flux Variationssupporting
confidence: 62%
“…This galaxy was observed twice with XMM-Newton in 2002 and 2013 and once with Chandra in 2010. Recently, Marchese et al (2014) have compared XMM-Newton and Suzaku data from 2002 and 2008. They fitted the data with a power law component transmitted through three absorbers (one neutral and two ionized), obtaining intrinsic luminosities of log(L(2−10 keV)) = 43.50 and 43.51, respectively.…”
Section: Appendix B: Notes and Comparisons With Previous Results For mentioning
confidence: 99%
See 3 more Smart Citations